IMPROVING QUALITY OF EDUCATION IN DEHASEN BENGKULU UNIVERSITY: FINANCING MANAGEMENT APPROACH - Suwarni; Soleh, Ahmad; Noviantoro, Rinto (STIE Kusuma Negara, 2019)
Higher Education is demanded to be able to provide quality graduates and have competitiveness both domestically and abroad. In realizing the implementation of quality education, universities continue to innovate and ensure the continuity of the tri dharma of higher education. This study aims to analyze the improvement of the quality of education at Dehasen University Bengkulu through a financing approach. This researcher uses a qualitative approach and the research method used is descriptive method. The results showed that the management of financing at Dehasen Bengkulu University included planning, implementation, and oversight and accountability. Funding for the implementation of education refers to a predetermined plan. Sources of funding come from students, ministries, foundations, UNIVED and research funds. The average use of funds includes operational funds for the learning process (72%), infrastructure investment (10%), investment in facilities (9%), investment in human resources (6 %), community service funds (1%), and research funds (2%). Some financial performance indicators show that most of the achievements are above the predetermined standards and targets. Financial management is monitored and reported on an ongoing basis. The existence of public trust, the government and agencies as well as the support of the foundation to be a supporter in financing management while the limited achievement of accreditation B can be one of the obstacles in financial management.